Impact of corruption and crime on smuggling: evidence from Iran - Mansouri, Amin; Afghah, Morteza (Penerbit Universiti Utara Malaysia, 2019)
The main purpose of this research is to investigate the size and the relationship between smuggling and crime indexes such as returned checks, corruption and drinking alcohol in Iran during the period 1984–2015 by using Multiple Indicators Multiple Causes (MIMIC) model and Maximum Likelihood Estimation (MLE) method. The results showed that among the crime indexes, divorce, drinking alcohol and corruption were positively correlated with smuggling, while another crime index, returned checks had a negative relationship with smuggling. Besides, all socio-economic cause variables on smuggling, including tariffs, misery index, illiteracy, gap of exchange rate, economic openness index and the size of government were found to increase smuggling. Furthermore, the findings showed that the cause variables on smuggling, including liquidity and energy consumption were positively correlated with smuggling.